ChemInform Abstract: Curtius‐Like Rearrangement of an Iron—Nitrenoid Complex and Application in Biomimetic Synthesis of Bisindolylmethanes. Issue 37 (August 2016) - Li, Dashan; Wu, Ting; Liang, Kangjiang; Xia, Chengfeng
Abstract: An iron(II)‐catalyzed Curtius‐like rearrangement involving the decomposition of an iron‐nitrenoid complex generated by cleavage of N—O bonds of functionalized heteroauxin hydroxamates is investigated.